The Pros and Cons of Different Types of Business Structures in India - Rushil Gupta (Innovative Research Thoughts, 2023)
Business is the exchange of goods and services between two or more parties, intending to make a profit. Businesses can take many forms, from small sole proprietorships to large multinational corporations. The purpose of a business is to provide value to its customers by meeting their needs and wants, while also generating profits for the business owners. Businesses are essential to the economy because they create jobs, generate income, and contribute to the overall growth and development of a country. To operate effectively, businesses require a well-defined structure. The structure of a business refers to the way it is organized and managed. The structure of a business can be influenced by various factors, such as its size, ownership, legal and regulatory requirements, and the nature of its operations. The structure of a business can have a significant impact on its success or failure.